EFEKTIVITAS PENGGUNAAN MODEL COURSE RIVIEW HORAY BERBASIS MEDIA WORDWALL TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK SD - Amara Qonita Nur Izzati; Dhina Cahya Rohim, Moh. Aris Prasetiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of Course Review Horay learning model based on Wordwall media on mathematics learning outcomes of elementary school students. The background of this study is based on the mathematics learning outcomes of students who are still not optimal, one of which is caused by the lack of variety in the use of learning models. The method used was pre-experiment with a one group pre-test-post-test design which was carried out on third grade students of Aisyiyah Multilingual Darussalam Elementary School Getasrabi. The research instruments were tests (pre-test and post-test), student response questionnaires, and observation sheets. The results showed a significant increase in post-test scores compared to the pre-test, with the average score increasing from 52.64 to 87.23. The paired t-test showed a significant effect of the learning model on learning outcomes. In addition, the calculation of N-Gain test showed a score of 0.73 which is included in the high category. The questionnaire results also showed that students responded positively to learning with the model. Based on the results of hypothesis testing, H₀ is rejected and H₁ is accepted. Thus, it can be concluded that the Course Review Horay model based on Wordwall media is effective in improving the mathematics learning outcomes of elementary school students.